A new species and new records of the genus Oideterus Thomson, 1857 (Coleoptera: Cerambycidae: Prioninae: Anacolini) from Colombia - Ascuntar-Osnas, Oscar (Zootaxa, 2018)
Oideterus farallonensis sp. nov. is described from Colombia and a detailed photographic record is presented. New locality records for O. andrarius (Galileo, 1987) are provided and a distribution map of the genus Oideterus is presented for the country.